Chromosome–level genome assembly of the seasonally polyphenic scorpionfly (Panorpa liui) - Jiuzhou Liu; Yuetian Gao; Shuangmei Ding; Shuai Zhan; Ding Yang; Xiaoyan Liu (Scientific Data)
Abstract Mecoptera is a small relict order of insects within the Holometabola. Panorpidae is the most speciose family in Mecoptera. They are also known as scorpion flies due to the enlarged and upward recurved male genital bulb. Panorpa liui Hua, 1997, a member of Panorpidae, is a bivoltine species of seasonal color polyphenism in the lowland plain of northeastern China. In this study, we applied PacBio HiFi and Hi–C sequencing technologies to generate a chromosome-level genome reference of P. liui. The assembled genome is 678.26 Mbp in size, with 91.3% being anchored onto 23 pseudo–chromosomes. Benchmarking Universal Single–Copy Orthologs (BUSCO) estimation reveals the completeness of this assembly as 95.1%. By integrating full-length transcriptome and homologs of related species, we generated full annotation of this assembly, yielding a total of 15,960 protein–coding genes, of these, 15,892 genes were anchored on the 23 chromosomes. The high-quality genome provides critical genomic resources for population genetics and phylogenetic research on Mecoptera. It also offers valuable information for exploring the mechanisms underlying seasonal color polymorphism.